Diapriinae (Hymenoptera, Diapriidae) da estação ecológica de Jatí, no município de Luiz Antônio - Oliveira, Ana Lígia Santos de [UNESP] (2014)
Diapriidae is cosmopolitan, include about 200 genera e 2000 species described in three subfamilies: Diapriinae, Belytinae e Ambositrinae. To Brazil are described about 30 genera e 80 species. Diapriinae get into 50 genera in three tribes: Psilini, Spilomicrini e Diapriini. This research aimed to study the Diapriinae of Brazilian savannah, riparian vegetation and savannah woodland vegetation from Estação Ecológica de Jataí (EEJ), Luis Antonio municipality, at São Paulo State, Brazil; In each ambient, the samples were taken with two Malaise traps (Townes 1972) and two sets of five yellow pan traps, between December 2006 and November 2009, the biological material was sent to the Laboratório de Sistemática e Bioecologia de Parasitoides e Predadores (LSBPP) da APTA, Ribeirão Preto, SP, where were identified the subfamilies and genera of Diapriidae through the identification keys proposed by Masner e Garcia (2002). Were collected 2610 (1621 female /62,1% e 989 male /37,9%) of Diapriinae of 20 genera, among which 634 of Doliopria Kieffer (24,29% of the total collected), 492 Coptera Say (18,85%), 323 Trichopria Ashmead (12,38%), 306 Idiotypa Förster (11,72%), 297 Acanthopria Ashmead (11,38%), 281 Basalys Westwood (10,77%), 192 Spilomicrus Westwood (7,36%), 19 Leucopria Masner & Garcia (0,73%), 18 Entomacis Förster (0,69%), 11 Szelenyiopria Fabritius (0,42%), 10 Monelata Förster (0,38%), 8 Megaplastopria Ashmead (0,31%), 5 Ortona Masner & Garcia (0,19%), 3 Caecopria Masner and Pentapria Kieffer (0,11% each), 2 Mimopria Holmgren, 2 Omopria Masner & Garcia and 2 Paramesius Westwood (0,08% each) and 1 Labidopria Wasmann and 1 Mimopriella Masner & Garcia (0,04% each). The Malaise trap captured 1378 of Diapriinae (52,8% of the total collected), result that was statistically different (p< 0,0001) of the observed with yellow pan traps 1232 (47,2%). The largest amount of Diapriinae was ...